Empower yourself with market driven and flexible ICT programmes at AeU - NA, NA (New Sabah Times, 2013)
ICT programme at SICT - ICT inculcates a variety of teaching and learning methods. ICT industry in Malaysia has always experienced shortage of highly skilled employees.